Organized smallholders’ knowledge and attitude toward palm oil farmland biodiversity and willingness to participate in sustainable palm oil certification in Felda Ayer Hitam, Kluang, Johor - Awang, Fatihah (2016)
Knowledge and attitudes towards biodiversity and willingness to participate in the certification of sustainable palm oil in Felda Ayer Hitam, Kluang, Johor were determined through the interview with smallholders. Therefore, a study was conducted in Felda Ayer Hitam, the oldest FELDA in Johor. Data were collected using structured questionnaires, through interviews organized smallholders at morning and evening in a month. Target respondents were 50 peoples. The questionnaire had three parts, the first part of the background of the respondents, the second part of the knowledge and attitudes towards biodiversity in oil palm farm and the third is the willingness of organized smallholders to participate in the certification of sustainable palm oil. One-sample T-test was used to compare the net monthly income of smallholders with previous research and compares with fees of RSPO. From this study, the majority of organized smallholder agreed to participate in the certification of sustainable palm oil because it will increase their net monthly income because sales of sustainable palm oil have more profitable than oil that is not sustainable. The organized smallholder also had a good knowledge in assessing the importance of biodiversity in oil palm plantations.